Effect of Acute Ramadan Fasting on Muscle Function and Buffering System of Male Athletes - Fashi, Mohamad (Healthcare (Basel), 2021)
The aim of this study was to investigate the effect of acute Ramadan fasting (RF) on the muscle function and buffering system. Twelve male athletes with 8 years of professional sports experience (age, 23.2 ± 1.3 years, body mass index: 24.2 ± 2.2 kg/m(2)) participated in this study. The subjects were tested twice, 3 weeks after the beginning of RF and 2 weeks after the end RF. Muscle function, buffering capacity, and rating of perceived exertion (RPE) were measured during and after RF by using the Biodex isokinetic machine, blood gas analyzer, and RPE 6–20 Borg scale, respectively. Venous blood samples for pH and bicarbonate (HCO(3)(−)) were measured during and after RF by using the Biodex isokinetic machine, blood gas analyzer, and RPE 6–20 Borg scale, respectively. Venous blood samples for pH and bicarbonate (HCO(3)(−)) were taken immediately after 25 repetitions of isokinetic knee flexion and extension. Measures taken during isokinetic knee extension during RF were significantly lower than those after RF in extension peak torque (t = −4.72, p = 0.002), flexion peak torque (t = −3.80, p = 0.007), extension total work (t = −3.05, p = 0.019), extension average power (t = −4.20, p = 0.004), flexion average power (t = −3.37, p = 0.012), blood HCO(3)(−) (t = −2.02, p = 0.041), and RPE (Z = −1.69, p = 0.048). No influence of RF was found on the blood pH (t = 0.752, p = 0.476). RF has adverse effects on muscle function and buffering capacity in athletes. It seems that a low-carbohydrate substrate during RF impairs muscle performance and reduces the buffering capacity of the blood, leading to fatigue in athletes.